“Poster girl”: The discourse constructing the image of “girls in distress” as existential epistemic injustice - Levin, Lia; Cohen Brafman, Maya; Alnabilsy, Raghda; Pagorek Eshel, Shira; Karram-Elias, Haneen (Frontiers in Psychiatry, 2022)
The present study is focused on understanding how the image of the girl designated ‘in distress’ in official regulations guiding the provision of public social services to girls in Israel can be structured. The study takes a qualitative approach, and employs the critical-feminist paradigm to the analysis and interpretation of discourse, combining thematic content analysis and deductive critical discourse analysis. Its main findings disclose an organized process of establishing the normative authorities dominating the discourse on public social services for girls; classifying groups of service recipients to which a girl can belong; constructing their forms; and ultimately circumscribing the girls thereto, determining the performative acts on which receiving state assistance is conditional. Through discursive maneuvers of construction, the image of the girl is ‘born’ as an undisputed ‘truth’ deriving from the deviance attached to her every move. In this trajectory, basic epistemic injustices are perpetuated and solidified, and a new form of epistemic injustice – existential epistemic injustice – is revealed. This process’s implications are proposed.